2017
DOI: 10.23822/eurannaci.1764-1489.14
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D levels in children with recurrent wheezing and relation to the phenotypes and frequency of wheezing

Abstract: Summary Background. Recurrent wheezing may be related to various reasons. There is a lack of knowledge about the effect of vitamin D status in the children with recurrent wheezing. The aim of this study is to compare the level of vitamin D between recurrent wheezing children and healthy controls, and to investigate the relationship between vitamin 21.66 ± 8.13 ng/mL (5.6-53) in the study group and 25.36 ± 10.17 ng/ mL (6-59) M. Dogru, L.P. Seren relative (mother, father, sibling) had allergic disease. Milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
4
3
0
Order By: Relevance
“…Vitamin D level is significantly lower in children with recurrent wheeze than control group as well as vitamin D status as severe deficiency, deficiency, and insufficiency significantly recorded in children with recurrent wheeze. This is in consistent to a study carried out by Dogru, etal 26 and in Sweden by Stenberg et al 27 who shows that preschool children admitted to hospital with acute wheeze had significantly lower levels of vitamin D than children with no wheeze in an age-matched control group. In the current study the mean serum calcium, phosphorus and alkaline phosphatase levels shows no statistically significant difference between patients and control group.…”
Section: Discussionsupporting
confidence: 91%
“…Vitamin D level is significantly lower in children with recurrent wheeze than control group as well as vitamin D status as severe deficiency, deficiency, and insufficiency significantly recorded in children with recurrent wheeze. This is in consistent to a study carried out by Dogru, etal 26 and in Sweden by Stenberg et al 27 who shows that preschool children admitted to hospital with acute wheeze had significantly lower levels of vitamin D than children with no wheeze in an age-matched control group. In the current study the mean serum calcium, phosphorus and alkaline phosphatase levels shows no statistically significant difference between patients and control group.…”
Section: Discussionsupporting
confidence: 91%
“…Vitamin D reportedly reduces eosinophilic airway inflammation in murine lung tissue [ 40 ] and sputum from asthma patients [ 41 ]. Even though the literature reports a positive correlation between sputum and serum eosinophilia [ 42 ], several articles mention that vitamin D supplements and serum 25-OH-VitD status do not seem to significantly influence serum eosinophils [ 18 , 43 ], similar to the finding reported in the current study. Our results can be explained by the fact that the link between the eosinophil count and serum 25-OH-VitD was only evaluated once, at the moment that the patient was included in the study, therefore offering only a snapshot of the inflammation, whereas monitoring the dynamics of the serum levels of both might yield a more accurate reflection of the evolution of inflammation during oral vitamin D 3 therapy [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, in many studies it has been reported that low levels of vitamin D may be a risk factor for recurrent wheezing. 22,23 Similarly, we found significantly lower vitamin D levels in children with recurrent wheezing compared to the control group.…”
Section: Discussionsupporting
confidence: 60%